Refractory Frontier: Intra-party Democracy in the Zambian Polity - John Bwalya; Owen B. Sichone (Modern Africa)
Despite the important role that intra-party democracy plays in democratic consolidation, particularly in third-wave democracies, it has not received as much attention as inter-party democracy. Based on the Zambian polity, this article uses the concept of selectocracy to explain why, to a large extent, intra-party democracy has remained a refractory frontier. Two traits of intra-party democracy are examined: leadership transitions at party president-level and the selection of political party members for key leadership positions. The present study of four political parties: United National Independence Party (UNIP), Movement for Multiparty Democracy (MMD), United Party for National Development (UPND) and Patriotic Front (PF) demonstrates that the iron law of oligarchy predominates leadership transitions and selection. Within this milieu, intertwined but fluid factors, inimical to democratic consolidation but underpinning selectocracy, are explained.